2018
DOI: 10.3389/fneur.2018.00987
|View full text |Cite
|
Sign up to set email alerts
|

Administration of Bone Marrow-Derived Mononuclear Cells Contributed to the Reduction of Hypoxic-Ischemic Brain Injury in Neonatal Rats

Abstract: Background/Objective: Perinatal hypoxic-ischemia (HI) causes neonatal death and permanent neurological deficits. Cell therapy using various cell sources has been recently identified as a novel therapy for perinatal HI. Among the available types of cell sources, bone marrow-derived mononuclear cells (BMMNCs) have unique features for clinical application. For example, stem cells can be collected after admission, thus enabling us to perform autologous transplantation. This study aimed to investigate whether the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…There is increasing evidence that stem cell therapy could have positive effects after a hypoxic-ischemic insult in the perinatal period. Several positive outcomes were identified in in vivo studies: improved functional outcome [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], increased angiogenesis [ 30 , 72 ], increased neurotrophic and growth factors levels [ 34 , 53 , 72 , 73 , 74 ], and cell proliferation [ 46 , 57 , 61 ]; reduction in the extension of brain damage [ 31 , 43 ,…”
Section: The Potential Of Stem Cell Therapy For Hiementioning
confidence: 99%
See 4 more Smart Citations
“…There is increasing evidence that stem cell therapy could have positive effects after a hypoxic-ischemic insult in the perinatal period. Several positive outcomes were identified in in vivo studies: improved functional outcome [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ], increased angiogenesis [ 30 , 72 ], increased neurotrophic and growth factors levels [ 34 , 53 , 72 , 73 , 74 ], and cell proliferation [ 46 , 57 , 61 ]; reduction in the extension of brain damage [ 31 , 43 ,…”
Section: The Potential Of Stem Cell Therapy For Hiementioning
confidence: 99%
“…Even though there were differences between the studies regarding the lesion severity and treatment protocol, the vast majority reported an improvement in motor and cognitive function after BM-MSCs administration [ 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 ]. The majority of the studies reported that BM-MSCs treatment decreased brain damage [ 54 , 56 , 58 , 59 , 60 , 61 , 62 , 63 , 67 ], prompting a decrease in apoptosis [ 54 , 64 , 73 ].…”
Section: The Potential Of Stem Cell Therapy For Hiementioning
confidence: 99%
See 3 more Smart Citations